Evaluation of a handheld clinical decision support tool for evidence-based learning and practice in medical undergraduates. - Johnston JM; Leung GM; Tin KYK; Ho L; Lam W; Fielding R (Medical Education, 2004)
INTRODUCTION: Handheld computers (PDAs) uploaded with clinical decision support software (CDSS) have the potential to facilitate the adoption of evidence-based medicine (EBM) at the point-of-care among undergraduate medical students. Further evaluation of the usefulness and acceptability of these tools is required. METHODS: All 169 Year 4 undergraduate medical students at the University of Hong Kong completed a post-randomised controlled trial survey. Primary outcome measures were CDSS/PDA usefulness, satisfaction, functionality and utilisation. Focus groups were also conducted to derive complementary qualitative data on the students' attitudes towards using such new technology. RESULTS: Overall, the students found the CDSS/PDA useful (mean score = 3.90 out of 6, 95% confidence interval (CI) = 3.78, 4.03). They were less satisfied with the functional features of the CDSS (mean score = 3.45, 95% CI = 3.32, 3.59) and the PDA (mean score = 3.51 95% CI = 3.40, 3.62). Utilisation was low, with the average frequency of use less than once per week. Although students reported a need for information in patient care at least once daily, they infrequently used the CDSS in a clinical setting (20.4 +/- 10.4% of the time), with an average information retrieval success rate of 37.6 +/- 22.1% requiring 63.7 +/- 86.1 seconds. Multivariable regression shows that higher perceived CDSS/PDA usefulness was associated with more supportive faculty attitudes, greater knowledge of EBM, better computer literacy skills and increased use in a clinical setting. Greater satisfaction with the CDSS/PDA was associated with increased use in a clinical setting and higher successful search rates. Qualitative results were consistent with these quantitative findings and yielded additional information on students' underlying feelings that may explain the observations. CONCLUSIONS: While PDAs uploaded with the CDSS are able to provide students with better access to high quality information, improvements in faculty attitudes, students' knowledge of EBM and computer literacy skills, and having the CDSS specially designed for undergraduate use are essential to increasing student adoption of such point-of-care tools.